Pengaruh Reward dan Punishment Terhadap Kinerja Pegawai Pada Dinas Pemadam Kebakaran dan Penyelamatan Kota Palopo - Khawas, Fawwas Amal; Munawir; Awaluddin, Satria; Imel; Febriansyah (Movere Journal, 2026)
This study aims to determine the effect of reward and punishment on employee performance at the Fire and Rescue Department of Palopo City. Employee performance is a crucial factor in determining the effectiveness of public services, particularly in fire handling and rescue operations. Rewards as a form of appreciation and punishments as a form of sanction are expected to influence employees' work motivation and productivity. This research employs a quantitative approach using a survey method by distributing questionnaires to 44 respondents selected incidentally. The data were analyzed using multiple linear regression analysis with the assistance of SPSS. The results show that both reward and punishment have a positive and significant effect on employee performance, both simultaneously and partially. Thus, the appropriate implementation of rewards and punishments can improve employee performance in carrying out their duties and responsibilities.